Rhinodrilus priscilae and Andiorrhinus (Amazonidrilus) caxiuana (Crassiclitellata, Rcrilidae) two new species from Caxiuanã National Forest - Hernández-García, Luis Manuel; Sousa, Sandriel Costa; Beckman, Ruana Aretha Farias Santiago; Pereira, Natália Jovita; Rousseau, Guillaume Xavier (Zootaxa, 2023)
The amazon forest is the habitat of a high species diversity of invertebrates and unfortunately the real richness had been underestimated. Earthworms’ inventories had been poor because difficult to describe new species. This study adds new records to eastern amazon of two new species belong Rhinodrilus and Andiorrhinus genera. R. priscilae n. sp. is another rare specimen of the genre having two pair of prostatoid glands. A. (Amazonidrilus) caxiuana differ of other species in size, the intestinal origin is in XXVIII and also has only one glandular mass associated to spermatheca.